FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGGUNAAN KARTU GSM (Global System for Mobile) PADA MAHASISWA STIE NOBEL INDONESIA MAKASSAR - Ridwan Ridwan (Jurnal Bisnis dan Kewirausahaan, 2019)
This study aims to determine how much influence the Product Quality has on the decision to use a GSM (Global System for Mobile) card. and to find out how much influence the price has on the decision to use a GSM (Global System for Mobile) card. and it can be concluded that Based on the results of the t test (partial) it is known that product quality has a positive but not significant effect on purchasing decisions based on the significance of 0.074 which is greater than 0.05 and the price has a positive and significant effect on purchasing decisions based on significance 0.001 which is smaller than 0.05